Comparison of deep and superficial abdominal muscle activity between experienced Pilates and resistance exercise instructors and controls during stabilization exercise - Moon, Ji-Hyun (J Exerc Rehabil, 2015)
Pilates and resistance exercises are used for lumbar stabilization training. However, it is unclear which exercise is more effective for lumbar stabilization. In our study, we aimed to compare surface muscle activity and deep muscle thickness during relaxation and spinal stabilization exercise in experienced Pilates and resistance exercise instructors. This study is a retrospective case control study set in the Exercise Prescription Laboratory and Sports Medicine Center. The participants included Pilates instructors (mean years of experience, 3.20±1.76; n=10), resistance exercise instructors (mean years of experience, 2.53±0.63; n=10), and controls (n=10). The participants performed 4 different stabilization exercises: abdominal drawing-in maneuver, bridging, roll-up, and one-leg raise. During the stabilization exercises, surface muscle activity was measured with electromyography, whereas deep muscle thickness was measured by ultrasound imaging. During the 4 stabilization exercises, the thickness of the transverse abdominis (TrA) was significantly greater in the Pilates-trained group than the other 2 other groups. The internal oblique (IO) thickness was significantly greater in the Pilates- and resistance-trained group than the control group, during the 4 exercises. However, the surface muscle activities were similar between the groups. Both Pilates and resistance exercise instructors had greater activation of deep muscles, such as the TrA and IO, than the control subjects. Pilates and resistance exercise are both effective for increasing abdominal deep muscle thickness.